OBSERVATIONS ON THE BIOLOGY OF LABEO GONIUS (HAMILTON) - Parameswaran, S; Selvaraj, C; Radhakrishnan, S (Indian Journal of Fisheries, 2011)
Observations on the biology of Labeo gonius (Hamilton) in confined watershave been made and the data on the different aspects have been analyzed anddiscussed.The length - weight relationship of the species can be expressed by theequation US'=0.000007153 L 3.0865. The monthly fluctuation in the conditionfactor of the adult fish was found to be related to the maturity cycle.L. gonius matures within a year. The ratio between males and femaleswas found to be 1:1.052. Macroscopic and microscopic examination of thegonads, ova diameter measurements and gonadosomatic index indicated thatmature fish become available from March to August, thÂ© peak being in May.The size frequency of ova in ovaries in different stages of maturity suggestedthat the species breeds only ones in a year. The statistical relationships betweenfecundity in relation to total length, total weight and ovary weight and ovaryweight in relation to total length have been established.From an exclusively plankton-feeding habit in the post-larval stage, thespecies changes over to a column and bottom-feeding habit in the juvenile stage,subsisting on vegetable matter, phyto and zooplankton organisms, mud and sand.The adult fish is predominantly a bottom feeder, the diet consisting of fresh anddecaying plant matter, mud and sand, phytoplankton and filamentous algae.Preliminary experiments indicated that the growth rate of L. gonius ispoor in comparison to major carps.